Health status of primary school children: study in urban slums of Lucknow - Verma, Neeti; Bajpai, Prashant Kumar (International Journal Of Community Medicine And Public Health, 2021)
Background: Children are the wealth of any nation because they constitute one of the population’s essential segments. Through school health services, morbidity patterns and nutritional status deficiencies are detected early and controlled to get a healthy and economically productive future generation. The present study was undertaken to assess the health status of primary school children in slum areas of Lucknow and find the morbidity pattern of the study population. Methods: A community-based cross-sectional study was conducted among 760 students of primary schools. A pre-designed, pre-tested, and semi-structured questionnaire was used as a study tool. Results: Most of the subjects 362 (47.7%) were in age group of 7-9 years, and were distributed almost equally in the classes from 1st to 5thstandard. About one fourth (26.8%) school children were underweight, whereas 5.6% school children were found overweight. Girls (34.0%) were found underweight more than the boys (20.8%). In contrast, more boys (8.8%) were overweight than girl students (2.6%). Conclusions: The common infirmities found were underweight (26.8%), dental caries (6.1%), anemia (14.9%), pediculosis (17.2%) and ear discharge (2.2%). Proper knowledge regarding and the creation of awareness amongst the school children, their families, about the causes and ill effects of the various morbidities are essential. Emphasis should be given to school children regarding prevailing morbidities amongst them by class teachers.